Collaborative board games a tool in developing social interest among 7 years old children - Tayag, Stephany S.
Young people play an important role in nation building since they will be the one who will take responsibility over the country as generations pass. The way the youth perceive society can make or break the future of the nation. With the youth's strong idealism, they can have the power to break the hegemonies and the injustices the country might face. Aside from believing in the power of young people, Rizal also hoped for a society where the people from an ethical community, working together for a common good that will benefit the whole nation.